Arnold Pick (1851-1924): a centenary appreciation - Andrew J Larner (Advances in Clinical Neuroscience & Rehabilitation, 2024)
2024 marks the centenary of the death of Arnold Pick (1851-1924). Many clinicians are aware of the name and of “Pick’s disease” although they may be unclear exactly who he was or what this terminology designates. This article seeks to give some brief biographical details, recap Pick’s key findings on “Pick’s disease”, and relate the latter to current thinking about the classification of frontotemporal dementia, an undertaking which prompts the consideration as to whether the eponym should stand or be laid to rest as now obsolete and superseded.